Drone production by the giant honey bee apis dorsata f. (hymenoptera: Apidae) - Bajaree Chuttong (2020)
© 2019 Universidade Estadual de Feira de Santana. All rights reserved. This study investigates male (drone) production by the giant honey bee (Apis dorsata F.). The entire brood population from 10 colonies were counted to determine the immature population of drones' relative to workers. After the condition of each cell was determined, the cell's position and content were noted using the Microsoft Excel platform. The contents of the brood comb, including eggs, larvae, prepupae, capped worker pupae, capped drone pupae, pollen storage cells and finally empty brood cells, were recorded. Results reveal the percent of pupal drones averaged 5.9 ± 6.8% with a range of 0.1 to 17.3%, of the total capped brood population. The size of the drone pupal population relative to the worker pupae was highly variable and displayed no correlation (r = 0.29). Drone pupae distribution was scattered throughout the brood comb in a random manner when drone pupal populations were low; in instances of higher drone production, the drone pupae appeared in banded patterns concomitant with the worker pupal distribution.